Effect of Formulated Plant Extract and Cypermethrin on Growth and Yield of Cucumber (Cucumis sativus L) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
This study set out to evaluate the performance of formulated plant extracts such as insecticide and cypermethrin on the growth and yield of cucumber (Cucumis sativus L). The treatments Azadrachta indica, and Jatropha curcas leaves formulated as insecticides, Control (Unsprayed), and Cypermethrin (Synthetic insecticide) were applied in the control of insect pests of cucumber, and the characteristics studied included the Number of leaves, Number of defoliated leaves, Numbers of fruit/plot and Numbers of damaged fruit. A field experiment was conducted in the teaching and Research Farm of Oyo State College of Agriculture and Technology, Igboora during the planting season of 2023. The Experiment was laid in a Randomized Complete Block Design and replicated three times. 200ml of formulated plant extract mixed with 800ml of water while 1ml of synthetic insecticide mixed with 1000ml of water was sprayed using a hand sprayer in the early hours of the day and this was done every week throughout the study. Results showed that the number of leaves and the numbers of fruit/plot were significantly (P < 0.05) greater for plants sprayed with the formulated plant extracts and cypermethrin compared to the unsprayed plot. Thus it indicated the effectiveness of the plant extracts in controlling insect pests of cucumber, which significantly improve the growth and yield of the crop. It was observed that the application of J. curcas leaves formulated as insecticide exhibited insecticidal activity when compared to synthetic insecticide and unsprayed plots. However, the application of A. indica also improves the growth and yield of cucumber when compared to the synthetic and unsprayed plot but is not as effective as J. curcas. These findings suggest that the formulated plant extract can be used to enhance the growth and yield of cucumber as an alternative to synthetic insecticides in the study area.
Keywords: Cucumber; Cypermethrin; Insect pests; Plant extract